Establishment of a mitotic model system by transient expression of the D-type cyclin in differentiated leaf cells of tobacco (Nicotiana benthamiana) - Xu, Jie (The New phytologist, 2020)
© 2019 The Authors. New Phytologist © 2019 New Phytologist Trust.